2014
DOI: 10.1007/s40141-014-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Management in Stroke Rehabilitation

Abstract: Oropharyngeal dysphagia is a frequent occurrence following stroke. The length of acute care hospitalization, however, has decreased over time with many individuals weak and frail upon admission for rehabilitation and possibly with continued dysphagia upon discharge. It is imperative that the swallowing therapist have a thorough understanding of evidence-based compensatory and exercise management strategies at all stages of recovery for patients with dysphagia following stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 81 publications
0
22
0
4
Order By: Relevance
“…Reports suggest differences in hyoid and laryngeal displacement but are mixed (Table 1) [11, 1518]. A more comprehensive understanding of covariant swallowing mechanics including hyoid and laryngeal movement, tongue base retraction, pharyngeal shortening, and head and neck extension could not only highlight the dysfunction underlying stroke-associated penetration and aspiration, but also suggest which treatment goals would be more salient [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest differences in hyoid and laryngeal displacement but are mixed (Table 1) [11, 1518]. A more comprehensive understanding of covariant swallowing mechanics including hyoid and laryngeal movement, tongue base retraction, pharyngeal shortening, and head and neck extension could not only highlight the dysfunction underlying stroke-associated penetration and aspiration, but also suggest which treatment goals would be more salient [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…VitalStim Therapy (VST) also known as Neuromuscular electrical stimulation (NMES) has been used for neuromuscular re-education in cases with oropharyngeal dysphagia. 19,20 The oral/facial electrical stimulation is applied to restore muscle function and Deep Pharyngeal Neuromuscular Stimulation (DPNS) for restoring reflexes within the pharynx. FDA (USA) protocol for dysphagia recommends use of electrode positioning on submental musculature.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory swallowing strategies include maneuvers, postures, and stimulation techniques used to improve swallowing efficiency and safety for a particular diet texture that would, without the use of strategies, be considered unsafe [22]. One study reported using multiple compensatory swallowing strategies in addition to tube feeding for swallowing intervention [11].…”
Section: Discussionmentioning
confidence: 99%